2017
DOI: 10.9734/arjass/2017/33064
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Demographic Factors and Pay Satisfaction on Career Satisfaction among Selected Employees in Redeemer’s University

Abstract: This study explores the influence of demographic factors and pay satisfaction and on career satisfaction among selected employees of Redeemer's University, Osun State, Nigeria. The study adopted a cross sectional survey research design and simple random sampling technique were used to select two hundred and twelve (212) participants (M=97 males; F= 115 females) among both academic and non-academic staffs. The Biodata form, Pay Satisfaction Scale (PSS) and Career Satisfaction Scale (CSS) were used to collect da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Psychological empowerment has long been studied as a key enabler of several career-related positive outcomes in the career management discipline such as career competencies (Kong et al, 2016) and career satisfaction (Arogundade & Arogundade, 2015). Despite this positive utility of psychological empowerment, its scope remains limited to the employees' current jobs and workplace phenomenon (Grabarski, 2021).…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Psychological empowerment has long been studied as a key enabler of several career-related positive outcomes in the career management discipline such as career competencies (Kong et al, 2016) and career satisfaction (Arogundade & Arogundade, 2015). Despite this positive utility of psychological empowerment, its scope remains limited to the employees' current jobs and workplace phenomenon (Grabarski, 2021).…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Dessler (2008), in his study, reported that public employees attributed the dissatisfaction with their careers to low benefits and salaries. Arogundade and Aremu (2017) claimed that salaries and bonuses help individuals to meet certain universal needs and, therefore, income, at least at lower levels, is an antecedent to career satisfaction and subjective well-being. Kim and Garman (2004) and Taylor and Vest (1992) believed that pay is an important reward used in motivating the behavior of employees at work.…”
Section: Remuneration and Work Stressmentioning
confidence: 99%
“…Kim and Garman (2004) and Taylor and Vest (1992) believed that pay is an important reward used in motivating the behavior of employees at work. Evidences suggested that unsatisfactory pay may lead to work stress, decreased career satisfaction, decreased motivation and performance, increased absenteeism and turnover intentions, and more pay-related grievances and lawsuits among workers (Arogundade & Aremu, 2017; CEB, 2015; Hedge & Rineer, 2017). Usman et al (2013) stated that the extent of financially distressed employees in a particular workplace depends primarily on their incomes.…”
Section: Remuneration and Work Stressmentioning
confidence: 99%
See 1 more Smart Citation